Shiftwork related health problems among nurses: a cross sectional study in a tertiary care centre of Central India - Lanjewar, Shilpa; Gawande, Bhagyashree; Narlawar, Uday; Likhitkar, Nikhil; Gawande, Bhushan (International Journal of Research in Medical Sciences, 2023)
Background: The nurses have an essential role to play in the provision of hospital healthcare services round the clock, which means that shifts are compulsory for them. Such work schedules have been related to numerous health problems including cardiovascular and gastrointestinal problems. This study has therefore been performed to assess the health problems associated with shift work among nurses. Methods: A cross‑sectional study among 375 nurses conducted in a tertiary care centre of central India. Nurses working in a shift duties and had worked for more than a year were included. Data were collected with the help of a pre designed pre tested questionnaire. Health problems related to shift work were assessed by using standard shift work index questionnaire. Blood pressure and blood sugar levels were measured. Data analysis was done using IBM SPSS Statistics Version 23. Results: Mean age of the study participants was 38.36±8.69 (23-57) years. Most frequently reported gastrointestinal symptom was disturbed appetite (33%) whereas most frequently reported cardiovascular symptom was headache (32.80 %). Common health problems reported by nurses after engaging in shift work were anaemia, chronic back pain, hypertension, varicose veins, diabetes, haemorrhoids, arthritis. Conclusions: Due to high proportion of health problems among nurses as compared to general population institutions must pay attention on their health and take measures for their well being.